Learning Survey During the Covid-19 Pandemic and Application Media Implications for Elementary School Teachers - Gandring Vemberia Ismayanti; Iqbal Miftakhul Mujtahid; Rian Vebrianto; Musa Thahir; Anita Tania (Universitas Pendidikan Ganesha, 2023)
The Covid-19 pandemic has resulted in social restrictions that have had a major impact on life. This study aims to analyze teachers' ability, especially elementary school teachers who are outside the city, to use online learning media. This research is survey research. The subjects of this study were 154 elementary school teachers who teach in cities. Sampling technique with purposive sampling technique. Data collection was carried out through an instrument in the form of a questionnaire. Data analysis techniques using qualitative and quantitative descriptive analysis. The results of a study on the ability of teachers to use online learning media applications for elementary teachers show that 93 people (60.4%) design media, sometimes (51.9%), and often (45.5%) to produce online learning media, and sometimes (49.4%) and often (42.9%) to use media. The aspect of facilities that support teachers to carry out online learning for elementary schools shows that 100% of the supporting facilities meet the requirements, including electricity, internet, textbooks, LKS, and interactive learning media facilities. There is a significant relationship between basic supporting facilities, interactive learning media, and learning aids for students. Parents and students must work together so that students are diligent in doing assignments and are more responsible in using IT.